2014
DOI: 10.1590/s0102-86502014000700009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous rate infusion of butorphanol in isoflurane-anesthetized calves

Abstract: PURPOSE:To assess the hemodynamic changes and bispectral index (BIS) following administration of a continuous rate infusion (CRI) of butorphanol in isoflurane-anesthetized calves. METHODS:Eight calves weighing 110 ± 12 kg were included in the study. Anesthesia was induced with 5% isoflurane in O 2 delivered via face mask and maintained with end-tidal concentration of 1.4%. IPPV was set to a peak inspiratory airway pressure of 15 cmH 2 O and respiratory rate of six breaths minute -1 . Forty minutes after the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Using the BIS, APREA et al (2014) clearly showed in a case report of the cardiopulmonary resuscitation of a propofol-anesthetized calf that the BIS values that were assessed had varied with cardiovascular function and that BIS was indicative of cerebral perfusion in cattle. ARAÚJO et al (2014) and reported mean BIS values of approximately 40 when conducting studies in calves using inhalation anesthesia with isoflurane combined with butorphanol infusion, and assessing BIS in isoflurane-anesthetized calves with or without CRI of lidocaine, respectively. Such values were slightly lower than those reported in this study, which is most likely related to the protocol that was used and to the difference in anesthetic plan.…”
Section: Discussionmentioning
confidence: 99%
“…Using the BIS, APREA et al (2014) clearly showed in a case report of the cardiopulmonary resuscitation of a propofol-anesthetized calf that the BIS values that were assessed had varied with cardiovascular function and that BIS was indicative of cerebral perfusion in cattle. ARAÚJO et al (2014) and reported mean BIS values of approximately 40 when conducting studies in calves using inhalation anesthesia with isoflurane combined with butorphanol infusion, and assessing BIS in isoflurane-anesthetized calves with or without CRI of lidocaine, respectively. Such values were slightly lower than those reported in this study, which is most likely related to the protocol that was used and to the difference in anesthetic plan.…”
Section: Discussionmentioning
confidence: 99%